Trans-Golgi Network-Located AP1 Gamma Adaptins Mediate Dileucine Motif-Directed Vacuolar Targeting in Arabidopsis - Wang, Xiangfeng; Cai, Yi; Wang, Hao; Zeng, Yonglun; Zhuang, Xiaohong; Li, Baiying; Jiang, Liwen (The Plant cell, 2014)
Membrane proteins on the tonoplast are indispensible for vacuolar functions in plants. However, how these proteins are transported to the vacuole and how they become separated from plasma membrane proteins remain largely unknown. In this study, we used Arabidopsis thaliana vacuolar ion transporteri (VIT1) as a reporter to study the mechanisms of tonoplast targeting. We showed that VIT1 reached the tonoplast through a pathway involving the endoplasmic reticulum (ER), Golgi, trans-Golgi network (TGN), prevacuolar compartment, and tonoplast. VIT1 contains a putative N-terminal dihydrophobic type ER export signal, and its N terminus has a conserved dileucine motif (E͟KQTL͟L͟), which is responsible for tonoplast targeting. In vitro peptide binding assays with synthetic VIT1 N terminus identified adaptor protein complex-1 (AP1) subunits that interacted with the dileucine motif. A deficiency of AP1 gamma adaptins in Arabidopsis cells caused relocation of tonoplast proteins containing the dileucine motif, such as VIT1 and inositol transporteri, to the plasma membrane. The dileucine motif also effectively rerouted the plasma membrane protein SCAMP1 to the tonoplast. Together with subcellular localization studies showing that AP1 gamma adaptins localize to the TGN, we propose that the AP1 complex on the TGN mediates tonoplast targeting of membrane proteins with the dileucine motif.